Treatment of patients with traumatic hand defects in Krasnodar region - A. M. Aristov; A. A. Afaunov; S. N. Kurinny; A. V. Shevchenko (Инновационная медицина Кубани)
Traumatic defects of hand tissues require mostly plasty covering with vascularised flaps. There are a great number of various variants with tissue complexes applied for hand reconstruction. In the present study we demonstrate our clinical experience with plasty substitution of traumatic defects in 35 patients with free and non-free radial flaps, insular digital flaps on the digital neurovascular bundle, flaps on the dorsal metacarpal arteries, cross digital flaps, non-free inguinal flaps and those from the anterior abdominal wall, temporal palm flaps. We showed reconstruction of fingers and hands with their soft tissues total and subtotal defects. The aim of this study is to point the indications for reconstructive plastic treatment in patients with traumatic hand defects with vascularised flaps application depending on the defect location and size.